Cerebrospinal fluid and intraoperative squash cytology of childhood ependymoma - Kalogeraki, Alexandra; Tamiolakis, Dimitrios; Moustou, Eleni; Panayiotides, Ioannis; Yannopoulos , Andreas; Vakis, Antonios; Katzilakis, Nikolaos; Stiakaki, Eftichia (Acta Biomedica Atenei Parmensis, 2021)
Ependymomas are glial neoplasms of central nervous system originated from the ependymal lining of the brain ventricles and spinal cord central canal, and rarely exfoliated into cerebrospinal fluid (CSF). In this case we report the cytomorphological and immunocytomorphological features of ependymoma in CSF and intraoperative squash preparations, confirmed by histology. Case report. The patient  was a nineteen months old female presented at the University hospital of Heraklion, Crete, in a hemicoma, and was intubated. Computed tomography, scanning and magnetic resonance imaging (MRI), were performed and a mass in the posterior fossa was found. A sample of cerebrospinal fluid (CSF) was sent for cytologic evaluation. A diagnosis of ependymoma was rendered, followed by tumor resection, during which intraoperative squash smears for cytologic interpretation were obtained. Cytological consultation disclosed a grade II ependymoma (WHO grade II), with focally anaplastic features (WHO grade III).